Synthesis and SAR studies of novel benzodiazepinedione-based inhibitors of Clostridium difficile (C. difficile) toxin B (TcdB). Issue 23 (15th December 2018) - Letourneau, Jeffrey J.; Stroke, Ilana L.; Hilbert, David W.; Cole, Andrew G.; Sturzenbecker, Laurie J.; Marinelli, Brett A.; Quintero, Jorge G.; Sabalski, Joan; Li, Yanfang; Ma, Linh; Pechik, Igor; Stein, Philip D.; et al.
Graphical abstract: Highlights: Highly potent C. diff. toxin B (TcdB) inhibitors identified. Improved plasma stability enabled compound progression into in vivo models of CDI. Compound11d efficacious in hamster survival model of CDI upon oral dosing. Abstract: Synthesis and structure-activity relationships (SAR) of a novel series of benzodiazepinedione-based inhibitors of Clostridium difficile toxin B (TcdB) are described. Compounds demonstrating low nanomolar affinity for TcdB, and which possess improved stability in mouse plasma vs. earlier compounds from this series, have been identified. Optimized compound11d demonstrates a good pharmacokinetic (PK) profile in mouse and hamster and is efficacious in a hamster survival model of Clostridium difficile infection.